HUBUNGAN PENGAWASAN DAN KINERJA KARYAWAN DIVISI TEKNISI PADA PT TRAKINDO UTAMA CABANG PEKANBARU - Risman, Risman; Sarumaha, Agus Henedra (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract This research is motivated by employee performance from time to time that needs to be improved, so employees must be able to improve their performance. This study aims to determine the effect of Work Supervision on the performance of the employees of the Technician Division of PT Trakindo Utama Pekanbaru Branch. In this study data were collected through a questionnaire of 34 employees. Quantitative analysis includes validity and reliability tests, classic assumption tests, hypothesis testing through t tests and analysis of coefficient of determination (R2) tests. The data analysis technique used is simple regression analysis, which serves to prove the research hypothesis. Hypothesis testing using the Coefficients test obtained t count of 5.300 and also t table of 2.036 which means t arithmetic 5.300> t table 2.036 and also the level of significance is 0.00 <0.05 so that the results of this study are supervision has a significant effect on employee performance in the Division PT Trakindo Utama Technician Pekanbaru Branch. The influence of supervisory variable (X) on performance (Y) is positive as evidenced from the result of b = 0.726 which means that every increase in one unit of monitoring variables will be able to increase the performance variable of the PT Trakindo Utama Pekanbaru Branch Technician Division by 0.726 units. The value of the determinant coefficient (R Square) of 0.467. This means that supervision contributes influence to the performance of the employees of the Technician Division of PT Trakindo Utama Pekanbaru Branch amounting to 46.70% while the remaining 53.30% is influenced by other variables outside the supervision variable.